Modeling Wireless LAN (WI-FI) in Kolej Latihan Telekom Utara, Taiping - Tajudin, Ramlee (2005)
Modeling an enterprise Wireless LAN is a new challenge even for experienced network architects. No company simply flips on the lights one morning and decides, it’s time to build Wireless LAN. Like any other IT decision, move to Wireless LAN technology has to be carefully thought out and tested to ensure that it meet their business requirements. Implementing Wireless network requires addressing three important key issues : technology option, deal with security and which vendor should we work with. Therefore, the purpose of this paper is to study the requirement of modeling Wireless LAN in academic building of Kolej Latihan Telekom Utara, Taiping.